Assessing Cybersecurity Threats and Awareness in Bosaso's Banking and Telecom Sectors - Buraale, Mohamed Abdirisak; T.K.A, Rahman; Fazilah, Che Fauzi (2024)
Cybersecurity is a critical concern for the banking and telecom sectors, which are prime targets for cyber threats. In Bosaso, Somalia, the increase digital technologies has outpaced the implementation of effective cybersecurity measures. This study aims to evaluate the current level of cybersecurity awareness among IT professionals in Bosaso's banking and telecom sectors and to identify key vulnerabilities and threats confronting these industries. A quantitative survey was conducted, targeting IT professionals in Bosaso's banking and telecom sectors. The survey assessed participants' awareness of cybersecurity threats, their confidence in existing security measures, and their experiences with cyber incidents. Data were analyzed using descriptive statistics and thematic analysis to elucidate common themes and patterns. The survey revealed that while the majority of IT professionals are aware of common cybersecurity threats, there is a significant lack of confidence in the adequacy of current security measures. Key vulnerabilities identified include inadequate employee training, outdated software, and insufficient investment in advanced security technologies. Furthermore, 65% of respondents reported experiencing at least one cyber incident in the past year. These findings underscore the urgent need for enhanced cybersecurity practices. The study highlights the critical need for improved cybersecurity training programs, substantial investment in modern security technologies, and the implementation of comprehensive cybersecurity policies in Bosaso's banking and telecom sectors. Addressing these issues is essential for safeguarding sensitive information and ensuring the resilience of these critical infrastructure.